Investment committee paper - Canada goose - Karberg, Darryl (2022)
This Investment Committee Paper discusses a potential leveraged buyout of Canadian luxury apparel brand Canada Goose. Founded in 1957, Canada Goose designs, manufactures, and distributes performance luxury apparel with a focus on winter-wear. Due to its strong brand equity, high profitability, and attractive growth opportunities, Canada Goose presents an attractive buyout target. By assessing the luxury apparel market and Canada Goose’s business model and its financials, an operating model is forecasted. A company valuation is proposed which is used as starting point for a leveraged buyout model. This paper concludes with potential exit strategies and suggests areas for due diligence.